Synthesis, Characterization and Biological Evaluation of N-3 Substituted Quinazolin-4(3H)-ones - Jini, J.P.; Devi, P.; Vijayabaskaran, M.; Selvam, P. (Asian Journal of Chemistry, 2026)
A series of 3-substituted-2-phenylquinazolin-4(3H)-one derivatives (4a-g) were designed and synthesized to examine the effect of different steric and electronic substituents on their chemical and biological properties. The target compounds were obtained in good yields of 64-78% by reacting 2-phenyl-4H-benzo[d][1,3]oxazin-4-one with substituted aromatic and heteroaromatic primary amines in glacial acetic acid. Structural characterization was carried out using FT-IR, 1H NMR and 13C NMR spectroscopy. The FT-IR data established the characteristic carbonyl stretching vibration of the quinazolinone moiety within the 1682-1670 cm−1 range, consistent with the resonance effects of the heterocyclic ring. The synthesized derivatives exhibited moderate to good concentration-dependent antioxidant activity in the DPPH assay, while their anti-inflammatory potential was assessed through the protein denaturation assay.